Exploring the Implementation and Impact of Blockchain Technology on Student Academic Data Management in Higher Education - Ainan Sekartika; M. Dirga Leandro (Journal Basic Science and Technology, 2024)
This research explores the implementation of blockchain technology in managing student academic data in higher education, investigating its potential benefits, challenges, and implications for theory, practice, and policy. Blockchain's decentralized, secure, and immutable nature offers significant advantages in enhancing data security, integrity, transparency, and student empowerment through self-sovereign identity systems. These benefits can streamline administrative processes, reduce operational costs, and improve trust among stakeholders. However, the research identifies several challenges, including technical complexities, scalability issues, interoperability with existing systems, regulatory compliance, and ethical considerations. Addressing these challenges requires robust technical infrastructure, stakeholder engagement, comprehensive training, and interdisciplinary collaboration. The study's findings have broad implications, prompting a reevaluation of traditional data governance theories and guiding higher education institutions in adapting their practices to leverage blockchain's strengths. This research provides a comprehensive analysis of blockchain's transformative potential in higher education, offering insights and strategies for successful implementation and fostering a more secure, transparent, and student-centric data management system.